Tumor Associated Macrophages: A Review with Institutional Study - Sreepreeti Champatyray1 , Priyanka Debta2 , Neeta Mohanty3 , Saurjya Ranjan Das4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aims: To study the expression of tumor-associated macrophages in different grades of squamous cellcarcinoma and find the association between their expression and local recurrence, metastasis.Methodology: Thirty tumor biopsy samples of oral squamous cell carcinoma in T1N0M0 and T2N0M0stages. Ten biopsy specimen of normal oral mucosa that are taken during minor oral surgical procedure withpatient consent.Result: Macrophages were found to have better specificity for local recurrence, metastasis, and survival.Further, higher expression of biomarkers was associated with shorter survival. We have analyzed thedifferential expression of MMP 9 in different grades of OSCC & compare their expression with differentTNM staging of tumors.Conclusions: Concluding this review of tumor-associated macrophages in comparison with OSCC cases.Since metastases are the principal cause of death in cancer patients, a greater understanding of the process oftumor invasion and metastasis is essential in leading to the identification of new therapeutic targets.